Dental Pulp Mesenchymal Stem Cells as a Treatment for Periodontal Disease in Older Adults - Beatriz Hernández-Monjaraz; Edelmiro Santiago-Osorio; Edgar Ledesma-Martínez; Itzen Aguiñiga-Sánchez; Norma Angélica Sosa-Hernández; Víctor Manuel Mendoza-Núñez (Hindawi Limited, 2020)
Periodontal disease (PD) is one of the main causes of tooth loss and is related to oxidative stress and chronic inflammation. Although different treatments have been proposed in the past, the vast majority do not regenerate lost tissues. In this sense, the use of dental pulp mesenchymal stem cells (DPMSCs) seems to be an alternative for the regeneration of periodontal bone tissue. A quasi-experimental study was conducted in a sample of 22 adults between 55 and 64 years of age with PD, without uncontrolled systemic chronic diseases. Two groups were formed randomly: (i) experimental group (EG) n=11, with a treatment based on DPMSCs; and a (ii) control group (CG) n=11, without a treatment of DPMSCs. Every participant underwent clinical and radiological evaluations and measurement of bone mineral density (BMD) by tomography. Saliva samples were taken as well, to determine the total concentration of antioxidants, superoxide dismutase (SOD), lipoperoxides, and interleukins (IL), before and 6 months after treatment. All subjects underwent curettage and periodontal surgery, the EG had a collagen scaffold treated with DPMSCs, while the CG only had the collagen scaffold placed. The EG with DPMSCs showed an increase in the BMD of the alveolar bone with a borderline statistical significance (baseline 638.82±181.7 vs. posttreatment 781.26±162.2 HU, p=0.09). Regarding oxidative stress and inflammation markers, salivary SOD levels were significantly higher in EG (baseline 1.49±0.96 vs. 2.14±1.12 U/L posttreatment, p<0.05) meanwhile IL1β levels had a decrease (baseline 1001.91±675.5vs. posttreatment 722.3±349.4 pg/ml, p<0.05). Our findings suggest that a DPMSCs treatment based on DPMSCs has both an effect on bone regeneration linked to an increased SOD and decreased levels of IL1β in aging subjects with PD.